The Specter of the Jews : Emperor Julian and the Rhetoric of Ethnicity in Syrian Antioch - Finkelstein, Ari, 1971- (Book collections on Project MUSE., 2018)
"In the generation after Constantine the Great elevated Christianity to a dominant position in the Roman Empire, his nephew, the Emperor Julian, sought to reinstate the old gods to their former place of prominence--in the face of intense opposition from the newly powerful Christian church. In early 363 CE, while living in Syrian Antioch, Julian redoubled his efforts to Hellenize the Roman Empire by turning to an unlikely source: the Jews. With a war against Persia on the horizon, Julian thought it crucial that all Romans propitiate the true gods and gain their favor through proper practice. To convince his people, he drew on Jews, whom he characterized as Judeans, using their scriptures, practices, and heroes as sources for his program and models to emulate. In The Specter of the Jews, Ari Finkelstein examines Julian's writings and views on Jews as Judeans, a venerable group whose religious practices and values would help delegitimize Christianity and, surprisingly, shape a new imperial Hellenic pagan identity"--Provided by publisher.